COMPOSITIONAL ANALYSIS OF THE SHORT STORY “INDIAN VILLAGE” - Durnazarova Mahliyo; Akhmedova Mehrinigor Bahodirovna (Journal of new century innovations, 2023)
Abstract. In this article we discussed the composition of the short story “Short term happiness of Francis Mackomber” by Ernest Hemingway.The bond between a father and son, as well as the accompanying rituals of passage into adult experience such as childbirth, losing innocence, and suicide, are the main topics of this book.